Role of School Leadership to Improve School Quality Through Hidden Curriculum - Mulyani, Heni; Tanuatmodjo, Heraeni (Universitas Pendidikan Indonesia, 2021)
AbstractThis study aims to explore the leadership role of school principals in maintaining and developing a hidden curriculum to improve school quality. The research was conducted in schools in the city of Bandung using a survey method. Data collection techniques used an open questionnaire. The results showed that the key to the success of school principals in achieving the objectives of the hidden curriculum refers to two aspects: (a) related to the character of school principals which can be seen in the integrity of female principals, leadership styles, managerial abilities of principals and competence of school principals related to the determinants of the success of the hidden curriculum which includes the authority of the school principal, the role of teachers in overseeing the implementation of the hidden curriculum, support from parents and school autonomy. Hidden curriculum that is formed the school character will improve the quality of the school.